Enhanced expression of ten‐eleven translocation 1 reverses gemcitabine resistance in cholangiocarcinoma accompanied by a reduction in P‐glycoprotein expression - Chuanxu Wang; Hua Ye; Lei Zhang; Yayu Cheng; Shifeng Xu; Ping Zhang; Zijie Zhang; Jimin Bai; Fangkang Meng; Lin Zhong; Guangjun Shi; Hao Li (Cancer Medicine)
Abstract Increasing evidence revealed that ten‐eleven translocation 1 (TET1) plays an important role in tumorigenesis and chemoresistance, but its functions in gemcitabine resistance in cholangiocarcinoma (CCA) remain unknown. This study aims to investigate the effect of TET1 on gemcitabine resistance in CCA and the possible effect on P‐glycoprotein (P‐gp) expression encoded by multidrug resistance (MDR) genes. We established two kinds of gemcitabine‐resistant CCA cell lines and confirmed its specific features. The expression of TET1 and P‐gp was evaluated in gemcitabine‐resistant CCA cells and their parental cells at mRNA and protein level by quantitative RT‐PCR and western blot analysis. After transfecting the gemcitabine‐resistant CCA cell lines with TET1 gene or siRNA, the cell viability test was obtained to verify the effect of TET1 on the sensitivity of CCA cells to gemcitabine. And then, the possible effect of TET1 on the expression of P‐gp was examined by western blot analysis. Xenograft tumor experiment was conducted to confirm the association between TET1 and P‐gp expression under gemcitabine chemoresistance. The associations between clinical outcomes of CCA patients with chemotherapy and TET1 expression were analyzed in 82 patients. The results showed that TET1 expression was significantly decreased, and P‐gp expression was increased in gemcitabine‐resistant CCA cells. Additionally, overexpression of TET1 augmented the sensitivity of CCA cells to gemcitabine and induced the decreased expression of P‐gp in gemcitabine‐resistant CCA cells. Furthermore, multivariate Cox regression analysis indicated that TET1 expression and TNM stage were independent risk factors (P < 0.001) for the clinical outcomes of CCA patients with chemotherapy. Additionally, Kaplan‐Meier survival and the log‐rank test showed that decreased expression of TET1 was associated with poorer prognosis of CCA patients with chemotherapy. These findings suggest that TET1 expression reverses gemcitabine resistance in CCA accompanied by a reduction in P‐gp expression. Thus, TET1 may be a promising target to overcome chemoresistance in CCA.